Culinary trails in popularizing ethnic cuisines - Jadwiga Topczewska; Jadwiga Lechowska; Joanna Kaszuba; Wanda Krupa (Journal of Ethnic Foods, 2022)
Abstract The aim of the article is to advance knowledge regarding the significant role played by culinary trail projects in promoting foods from ethnic groups residing in Podkarpackie, Poland’s southeastern region. Podkarpackie’s culinary heritage, cultural identities, and the specificity of its cuisine that contribute to the region’s touristic potential are presented. Traditional and regional dishes of Podkarpackie are characterized by their originality and rich flavors, variety, and simplicity of preparation. They contribute to the region’s tourist attractions. Many restaurants in Southeast Poland offer regional dishes, such as kwaśnica, fuczki, and pierogi with various fillings or stuffed cabbage rolls. Culinary trails can be a critical factor in promoting not only the region’s ethnic food but its related culture and art as well.